2012
DOI: 10.9775/kvfd.2012.6522
|View full text |Cite
|
Sign up to set email alerts
|

Zom Koyunlarının Morfolojik Özellikleri

Abstract: ÖzetBu araştırma, Türkiye'de Diyarbakır ili yakınlarında bulunan Karacadağ'ın yüksek rakımlı yerlerinde yetiştiriciliği yapılan Zom koyunları üzerinde yürütülmüş bir tanımlama çalışmasıdır. Anahtar sözcükler: Zom koyunu, Morfolojik özellikler, Yapağı rengi Morphological Characteristics of Zom Sheep SummaryThis research was a descriptive study and carried out on Zom sheep raised in the mount Karacadağ province in Diyarbakir, Turkey. The study was conducted to determine some morphological characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…Statistically significant correlation coefficients were also observed between body weights and SH, LF, LH, and HL. Correlation coefficients found in this study were in accordance with those reported for other species such as sheep (Turgay et al, 1999;Koncagül et al, 2012), goat (Cam et al, 2010), and cattle (Koç and Akman, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Statistically significant correlation coefficients were also observed between body weights and SH, LF, LH, and HL. Correlation coefficients found in this study were in accordance with those reported for other species such as sheep (Turgay et al, 1999;Koncagül et al, 2012), goat (Cam et al, 2010), and cattle (Koç and Akman, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…This sheep was first identified and described, and its morphological characteristics were reported 3 based on the results of a project supported by General Directorate of Agricultural Researches and Politics (GDARP). They reported that average live weights, wither heights and body lengths of mature males and females of this sheep were 71.7±2.67 kg and 48.8±0.57 kg, 77.1±2.01 cm and 68.3±0.43 cm, 65.4±1.16 cm and 60.3±0.25 cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This length was determined to be shorter than Kıvırcık rams (36.4 cm) and ewes (35.3 cm) in a study previously reported. It is also shorter than Sakız (Chios), Gökçeada (Imroz), Karayaka, Zom, Karagül, Tuj, Çine Çaparı breeds (Özcan, 1970a;Anonymous, 2009, Erol andAkçadağ, 2009;Koncagül et al, 2012).…”
Section: Resultsmentioning
confidence: 93%
“…A study reported that the wither height of Kıvırcık is 64 cm and 69 cm for ewes and rams, respectively Özcan (1970a and 1970b) and Anonymous (2019) found these values as 66 cm and 65 cm for the Kıvırcık sheep. The withers height of Yalova genotype is higher than Akkaraman, Morkaraman, Dağlıç, İvesi (Awassi), Çine Çaparı, Güney Karaman, Karagül, Tuj, Herik, Karayaka, Gökçeada (Imroz), Pırlak, Zom breeds, similar to Karya, Sakız (Chios), Hemşin, Norduz, Karacabey Merino and lower than Kangal Akkaraman (Yılmaz ve ark., 2011;Koncagül et al, 2012;Yılmaz et al, 2013;Özbeyaz et al, 2018;Anonymous, 2019). x Back height, rump width, body length, rump width, chest width, chest depth and chest girth of Yalova genotype was higher than the reported values for Kivircik sheep.…”
Section: Resultsmentioning
confidence: 99%